Strategies and factors to promote research in primary care in Portugal: a cross-sectional study - Morgado, Maria Beatriz (2025)
© Copyright (c) 2025 Acta Médica Portuguesa. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License. All the articles published in the AMP are open access and comply with the requirements of funding agencies or academic institutions. The AMP is governed by the terms of the Creative Commons ‘Attribution – Non-Commercial Use - (CC-BY-NC)’ license, regarding the use by third parties.